The crushing of Syria's civil actors: Survival of grassroots structures is crucial for country's future - Petra Becker; Friederike Stolleis (Stiftung Wissenschaft und Politik (SWP), 2016)
The Syrian regime's strategy of using sieges and bombardments to force rebel-held areas to surrender is bringing it closer to its goal of eliminating independent civil-society engagement and alternative governance structures. Over the past six years, civil structures - that is, non-state non-military organisations and institutions - have been established and consolidated across Syria in areas out of government control to organise local affairs and provide the most essential community services. With the international debate on Syria concentrating on local military developments and regional power struggles, Syria's civil actors have been shifted out of focus. However, the marginalisation of these local and decentralised actors and structures represents a major risk for Syria's future. They not only constitute the bedrock for implementing any potential political agreement on the ground, they are also crucial for providing Syrians with an alternative to so-called Islamic State (IS) and other Islamist groups, which cannot be fought successfully by military means alone. (SWP Comments)
Keywords: 320